2007
DOI: 10.1007/s10822-007-9114-2
|View full text |Cite
|
Sign up to set email alerts
|

Surflex-Dock 2.1: Robust performance from ligand energetic modeling, ring flexibility, and knowledge-based search

Abstract: The Surflex flexible molecular docking method has been generalized and extended in two primary areas related to the search component of docking. First, incorporation of a small-molecule force-field extends the search into Cartesian coordinates constrained by internal ligand energetics. Whereas previous versions searched only the alignment and acyclic torsional space of the ligand, the new approach supports dynamic ring flexibility and allatom optimization of docked ligand poses. Second, knowledge of well estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
502
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(519 citation statements)
references
References 45 publications
7
502
0
2
Order By: Relevance
“…The ligand-protein interaction energy was first evaluated using the energy scoring functions of the two docking programs GOLD (23) and Surflex (24,25). The scoring functions of these two programs lend themselves well to the current protein-ligand system given that the nature of the ligand-binding pocket is mostly hydrophobic with a few hydrogen bonding sites.…”
Section: Scoring 20e and Pona Inside The Ecr Ligand-binding Pocketmentioning
confidence: 99%
“…The ligand-protein interaction energy was first evaluated using the energy scoring functions of the two docking programs GOLD (23) and Surflex (24,25). The scoring functions of these two programs lend themselves well to the current protein-ligand system given that the nature of the ligand-binding pocket is mostly hydrophobic with a few hydrogen bonding sites.…”
Section: Scoring 20e and Pona Inside The Ecr Ligand-binding Pocketmentioning
confidence: 99%
“…Molecular docking studies were carried out to understand the binding mode of the synthesized adamantyl derivatives 1-26 inside each of the cholinesterase enzymes using the Surflex-Dock package of Sybyl7.3 [25][26][27] software. Surflex is a fully automatic, flexible molecular docking algorithm that combines the scoring function from the Hammerhead docking system with a search engine that relies on a surface-based molecular similarity method as a means to rapidly generate suitable putative poses for molecular fragments.…”
Section: Preparation Of Protein Targetsmentioning
confidence: 99%
“…In unpublished research, benchmarking Surflex-Dock [234,244] with three other common molecular docking programs, MolDock [245], DOCK [226], and Autodock [227], we found that Surflex-Dock consistently reproduced predicted compound binding modes as illustrated by compound/receptor crystal structures to a greater degree than the other docking programs. The SurflexDock [234,244] method is centered on development of a protomol, a pseudomolecule used to virtually define the binding site targeted on the protein structure. This proto mol can be generated based on available ligands, inhibitors or partner proteins or development can be designed based on a defined series of target residues composing an active site.…”
Section: Structure Based Drug Design Is An Effective Technique For Idmentioning
confidence: 86%
“…Our prior experience with the Surflex-Dock [234,244] docking program has demonstrated that this program is highly amenable to high-throughput virtual screening. In unpublished research, benchmarking Surflex-Dock [234,244] with three other common molecular docking programs, MolDock [245], DOCK [226], and Autodock [227], we found that Surflex-Dock consistently reproduced predicted compound binding modes as illustrated by compound/receptor crystal structures to a greater degree than the other docking programs.…”
Section: Structure Based Drug Design Is An Effective Technique For Idmentioning
confidence: 99%
See 1 more Smart Citation